A Review on Security and Privacy of Smart Cities - Abdulhakim Alsaiari; Mohammad Ilyas (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Smart cities are expected to provide better services to citizens and urban environments, and to enhance the quality of their daily life. By utilizing smart technologies, Smart cities can deal with the emerging urbanization issues and promote sustainable development. Despite this, security and privacy issues are considered an obstacle which can impact the success of such emerging technologies and smart systems in smart cities. However, to fully leverage the benefits of smart systems and promote their further development, it's imperative to understand the security and privacy threats that weaken systems and make them vulnerable to be attacked. Motivated by these factors, this literature review provides a useful comprehensive combination of related literatures on smart cities challenges by technically analyzing various results. This review also discusses several components of smart cities such as transportation, governance, people, living, economy, innovative architecture, and associated knowledge and ideas. This paper also aims to critically examine various existing and deploying security and privacy protection methods for smart cities. Finally, we highlight several unresolved challenges and suggest future research possibilities and current security requirements, which may help building secured, privacy-protected, and stable smart cities.